Pengaruh Moralitas Individu, Kesesuaian Kompensasi, Proteksi Awig-Awig Desa Adat dan Asimetri Informasi terhadap Kecendrungan Kecurangan (Fraud) pada Lembaga Perkreditan Desa (LPD) di Kabupaten Buleleng - Cahyaningsih, Ni Ketut; Atmadja, Anantawikrama Tungga (Vokasi : Jurnal Riset Akuntansi, 2021)
Abstract This study aims to examine the effect of individual morality variables, compensation suitability, traditional village awig-awig protection and information asymmetry on the tendency of fraud at the Village Credit Institution (LDP) in Buleleng Regency. This study uses a quantitative approach. The research sample consisted of 64 respondents consisting of the Chair and staff of the LPD finance or bookkeeping department from 32 LPD samples in Buleleng Regency, which were determined by the Purposive Sampling method. The type of data used is a questionnaire distributed directly to the respondents. Technical analysis of the data used is multiple linear regression analysis and data presentation assisted by SPSS 26.0 for windows program. The results of this study indicate that individual morality has a negative and significant effect on the tendency of fraud at the Village Credit Institution (LPD), the suitability of compensation has a negative and significant effect on the tendency of fraud at the Village Credit Institution (LPD) for the protection of traditional village awig-awig. has a negative and significant effect on the tendency of fraud at the Village Credit Institution and information asymmetry has a positive and significant effect on the tendency of fraud at the Village Credit Institution (LPD) in Buleleng Regency. Keywords : individual morality, compensation suitability, protection of traditional village awig-awig, information asymmetry, tendency to fraud